Answer:
Given equation of a parabola is,
![f(x)=x^2-2x+3](https://img.qammunity.org/2023/formulas/mathematics/college/axeu4g769qvmvuaybn00h0zivawz131nkc.png)
To find the vertex of the parabola.
we know that,
Equation of the parabola is,
![y=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/97p0xsjs0cwme4ddvwkim2cbbqprhnlhsv.png)
where (h,k) is the vertex of the parabola.
we know that f(x)=y, the equation becomes,
![y=x^2-2x+3](https://img.qammunity.org/2023/formulas/mathematics/college/moq61hx6kjyq9d2rxm97y9tu4z3fqhqsoq.png)
To rewrite the above equation in the required format, adding and subtracting by1, we get
![y=x^2-2x+1-1+3](https://img.qammunity.org/2023/formulas/mathematics/college/z8nmqx2xc14px88e5x1ickauijgm3y05t8.png)
![y=(x-1)^2+2](https://img.qammunity.org/2023/formulas/mathematics/college/eajr1e109lce1hu2ocl5ccyza5baso4l6x.png)
we get the vertex as (1,2)
Vertex is (1,2)
y-intercept:
when x=0, we get y=3
y-intercept is y=3.
Answer is:
Vertex is (1,2) an y-intercept is y=3.